Ответ: -3 .
Пошаговое объяснение: y=(x²+ 3)/(x-1) ; xЄ[ -3 ; 0] ;
1) y' = [2x(x-1) - 1*(x²+ 3)]/(x-1)²=( x²-2x-3)/(x-1)²=[(x+1)(x-3)/(x-1)²;
2) y' = 0 ; при x=-1 ; x =3 ; x≠ 1 ∉[ -3 ; 0] ;
y(-3)=-3 ; y(-1) = -2 ; y(0 )=-3 .
Найменше значення функції на дагному проміжку дорівнює -3 .
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ: -3 .
Пошаговое объяснение: y=(x²+ 3)/(x-1) ; xЄ[ -3 ; 0] ;
1) y' = [2x(x-1) - 1*(x²+ 3)]/(x-1)²=( x²-2x-3)/(x-1)²=[(x+1)(x-3)/(x-1)²;
2) y' = 0 ; при x=-1 ; x =3 ; x≠ 1 ∉[ -3 ; 0] ;
y(-3)=-3 ; y(-1) = -2 ; y(0 )=-3 .
Найменше значення функції на дагному проміжку дорівнює -3 .